Identification of phasiRNAs and their drought‐ responsiveness in Populus trichocarpa. Issue 20 (4th October 2016) - Shuai, Peng; Su, Yanyan; Liang, Dan; Zhang, Zhoujia; Xia, Xinli; Yin, Weilun
Abstract : Phased, secondary, small interfering RNA (phasiRNA) perform essential biological functions in plants. However, limited information is available on the role of phasiRNA genes in Populus (poplar), especially during drought stress. In this study, we identified 20 PHAS loci generating 91 phasiRNA in the genome of the model forest tree Populus trichocarpa ( P. trichocarpa ; western balsam‐poplar) using the control and drought libraries. Our analysis indicated that six PHAS (PtPHA14‐20) initiated by two Populus ‐specific miRNAs (miR6445 and miR6427) were specific to Populus . In addition, a total of 47 phasiRNA were found to be drought responsive, and five of them were confirmed by RT‐qPCR. The phase cleavage of three PHAS loci by miRNA, and degradation of nine transcript targets by phasiRNA were experimentally confirmed based on degradome data. The identification of these Populus phasiRNA will contribute to a better understanding of their function and regulation during drought stress. Abstract :